2015
DOI: 10.4028/www.scientific.net/kem.651-653.1204
|View full text |Cite
|
Sign up to set email alerts
|

Economical Comparison of Cryogenic vs. Traditional Turning of Ti-6Al-4V: A Case Study

Abstract: Due to their poor machinability, titanium alloys need to be worked at low cutting speeds to prevent a fast tool failure caused by the very high temperatures that are reached at the tool-chip interface. As demonstrated by previous works by the authors, an improvement of productivity for Titanium alloys can be obtained by adopting cryogenic cooling during the machining operations.The present work shows the features of a toolholder specifically designed for cryogenic adduction in turning operations, following Hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…14 -16 These discrepancies can be partially attributed to the different compositions of Ti-6Al-4V used. 5 The borderline cooling rate for the diffusion-controlled β → α transformation is below about 20°C/s. 14 -16 Above 20°C/s, either the composition-invariant β → α m massive transformation occurs, where diffusional activity occurs mainly at the advancing interfaces, 25 or the composition-invariant diffusionless β → α ′ martensitic transformation occurs.…”
Section: Macro-and Microstructural Characteristics Of Am Ti-6al-4vmentioning
confidence: 99%
“…14 -16 These discrepancies can be partially attributed to the different compositions of Ti-6Al-4V used. 5 The borderline cooling rate for the diffusion-controlled β → α transformation is below about 20°C/s. 14 -16 Above 20°C/s, either the composition-invariant β → α m massive transformation occurs, where diffusional activity occurs mainly at the advancing interfaces, 25 or the composition-invariant diffusionless β → α ′ martensitic transformation occurs.…”
Section: Macro-and Microstructural Characteristics Of Am Ti-6al-4vmentioning
confidence: 99%
“…11 At the same time, benefits like clean and neat machining environment, removal of produced chips from cutting zone due to high pressure of cryogenic jet, no smoke or fume, and no oil or liquid cutting fluid spattered over the surfaces are attained by the application of cryogenic coolant. 12 In addition, the cost-related issue has been reported by Tirelli et al, 13 where it has been shown that cryogenic cooling incurs reduced cost than traditional wet cooling and improves tool life which eventually increases the machining productivity. For these reasons, cryogenic cooling by LN 2 has presented itself as a tenable solution to conventional cutting fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are the most representative example, being advanced structural materials, characterized by outstanding properties such as high strength-to-weight ratios, fracture toughness, corrosion resistance (immunity to seawater), and biocompatibility, but also affected by major technological drawbacks in terms of machinability, such as the extreme reactivity and the low thermal conductivity [3,4]. Only low-speed machining of forged titanium has been successfully employed over history, resulting in more than half of the raw materials wasted as scrap [5,6].…”
Section: Introductionmentioning
confidence: 99%